A narrative review of current and emerging MRI safety issues: What every MRI technologist (radiographer) needs to know. Issue 2 (9th September 2021) - Mittendorff, Lisa; Young, Adrienne; Sim, Jenny
Abstract: Magnetic resonance imaging (MRI) has been traditionally regarded as a safe imaging modality due to the absence of ionising radiation. However, MRI is a source of potential hazards with a variety of risks including, but not limited to, those associated with the various electromagnetic fields used for imaging. All MRI technologists (radiographers) require sound knowledge of the physical principles of the MRI scanner and must understand the associated safety risks and how to avoid adverse events from occurring. MRI technologists now assume more responsibility in clinical decision‐making, and their knowledge base has consequently had to expand significantly. In addition, rapid advancements in MRI technology and other correlated areas such as medical implant technology, and the associated increase in MRI safety issues, place increasing demands on the MRI technologist to constantly keep abreast of current and future developments. This article reviews current and emerging MRI safety issues relevant to the three MRI electromagnetic fields and highlights the key information that all MRI technologists should be fully cognisant of to ensure competent and safe practice within the MRI environment. Abstract : Rapid advancements in MRI technology and other correlated areas such as medical implant technology, and the associated increase in MRI safety issues, places increasing demands on the MRI technologist to maintain up‐to‐date knowledge and to constantly keep abreast of future developments. This article reviews current and evolving MRI safety issues and summarises the key information that all MRI technologists should be fully cognisant of to ensure competent practice and the safety of patients, staff and other personnel within the MRI environment.